Ex post: The investment performance of collectible stamps☆ - Dimson, Elroy; Spaenjers, Christophe (Journal of Financial Economics, 2011)
This paper uses stamp catalogue prices to investigate the returns on British collectible postage stamps over the period 1900–2008. We find an annualized return on stamps of 7.0% in nominal terms, or 2.9% in real terms. These returns are higher than those on bonds but below those on equities. The volatility of stamp prices approaches that of equities. Stamp returns are impacted by movements in the equity market, but the systematic risk of stamps remains low. Stamps partially hedge against unanticipated inflation. Estimates of average after-cost returns for individual investors show that stamps may rival equities in terms of realized performance.